Staff perspectives toward quality management practices at UNITI College, Pasir Panjang, Port Dickson, Negeri Sembilan / Azizul Abbas and Mohd Hijan Faiz Haddi - Abbas, Azizul; Haddi, Mohd Hijan Faiz (2010)
Quality management practices in organization are the prerequisite in seeking for achieved high performance. One of the tools used by many organizations including Higher Education Providers (HEP) is Malcolm Baldrige National Quality Award Criteria (MBNQA). UNITI College in Port Dickson, Negeri Sembilan is the one of HEP that have their own objective to get ISO certification by applying quality management practices based on MBNQA education for excellence criteria's. The MBNQA criteria highlighted in this study are Leadership, Strategic Planning, Customer and Market Focus, Measurement, Analysis, Knowledge Management and Business Result. The purpose of this research is to assist the management of UNITI College in implementing quality management practices at their college before they applied for ISO certification. The significances of this research covered the top management, academic staff, student and researcher.